Process-based information systems: technological infrastructure and development issues - Pereira, José Luís (2016)
Now, more than ever, organizations need information systems which may be quickly developed, rapidly reconfigured, and easily maintained. In this paper, we describe a specific IT infrastructure, inspired in the concept of business process, and mainly based on the functionalities provided by collaborative and workflow technologies, which might fulfill those needs. This infrastructure facilitates the construction of distributed IT solutions, in a component-based fashion. We argue that these solutions (Process-Based Information Systems - PBIS), allows organizations to quickly respond to changing business requirements and, moreover, simplifies the integration of new IT artefacts. In the context of PBIS, we propose a set of development requirements.